Attitudes, peer pressure and exposure toward action movies contribute to the risky motorcyclists’ behaviour - Othman, Nur Ain Amalia (2023)
Traffic accidents are a worldwide tragedy with an ever-rising trend. The main intention of this paper is to examine the relationship between the attitude of the rider, peer pressure and exposure towards action movies with risky motorcyclists’ behaviour. Researchers can see the trend of fatalities and injuries due to traffic accidents is increasing day by day. In 2022 itself, there were a sum of 545,588 traffic accidents reported and a total of 6,080 deaths. An average of 1,494 accidents per day or an accident per minute in Malaysia. Previous research has primarily relied on cross-sectional data and thus focused on several groups of respondents, such as young motorcyclists. This study focused on all the types of motorcyclists. A total of 166 respondents were collected from a questionnaire that was randomly distributed. Data was analyzed using SPSS software using correlation and multiple regression methods to identify the relationship between the variables. From the findings, researchers can conclude that the attitude of the rider and peer pressure have a significant association with risky motorcyclists’ behaviour, whereas exposure toward action movies does not show significant relationships with the risky motorcyclists’ behaviour. Therefore, this study will help optimize the work of authorities by systematically identifying the causes of risky motorcyclists’ behaviour and developing relevant ideas to address this issue.